The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/diagnostics11071210
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Chitinases as Biomarkers for Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative neuromuscular disease that affects motor neurons controlling voluntary muscles. Survival is usually 2–5 years after onset, and death occurs due to respiratory failure. The identification of biomarkers would be very useful to help in disease diagnosis and for patient stratification based on, e.g., progression rate, with implications in therapeutic trials. Neurofilaments constitute already-promising markers for ALS and, recently, chitinases have emerged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…To our knowledge, this study is the first to associate CHIT1 expression with HAM/TSP development. Altered levels of CHIT1 in the CSF have been shown as a biomarker for other neurodegenerative disorders, such as Alzheimer’s disease, amyotrophic lateral sclerosis (ALS), and multiple sclerosis ( 41 43 ). In ALS, it was observed an association between CSF CHIT1 levels and both disease severity and progression ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, this study is the first to associate CHIT1 expression with HAM/TSP development. Altered levels of CHIT1 in the CSF have been shown as a biomarker for other neurodegenerative disorders, such as Alzheimer’s disease, amyotrophic lateral sclerosis (ALS), and multiple sclerosis ( 41 43 ). In ALS, it was observed an association between CSF CHIT1 levels and both disease severity and progression ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that CHIT1 was intrathecally produced. In ALS, controversial results indicate that only CSF CHIT1 levels or both CSF and serum levels are useful as disease biomarker ( 43 , 44 ). However, the lack of paired CSF and serum samples in these studies might limited to obtain consistent conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of studies on CHIT1 corroborated previous findings that inflammatory components are involved in the death of motor neurons, and suggested that CHIT1 expression levels correlate with ALS progression and prognosis, i.e., higher CHIT1 levels lead to shorter survival time. In addition, an interesting study in 2021 found that CHIT1 was significantly negatively correlated with the respiratory function index of forced vital capacity (FVC), which is often used to measure potential respiratory damage in patients with ALS and is a predictor of survival and disease progression ( 19 ). Therefore, these studies emphasized the idea that measuring CHIT1 has advantages with regard to monitoring disease progression, predicting survival time, and potentially evaluating treatment response in patients with ALS.…”
Section: Chitinasementioning
confidence: 99%
“…Chitinases are produced by astrocytes and microglia and play a role in the nervous system's immune response [37]. CHIT1, CHI3L1, and CHI3L2 have been found to be elevated in the CSF of patients with ALS, with levels correlating with disease progression [37][38][39][40][41][42].…”
Section: Key Proteinsmentioning
confidence: 99%